KOORDINASI MATA , TANGAN, TINGGI BADAN DAN POWER TUNGKAI TERHADAP KEMAMPUAN SHOOTUNDERBASKET - NOWO TRI PURNOMO (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2015)
This study is aimed at knowing the coordination of eyes and hands also the height of body and heel power with shoot underbasket ability.This study is a correlation one, using survey method with test technique and measurement. The population of this study were 40 students. Meanwhile the instrument used was heel power test with vertical jump test, coordination test of hands by bouncing the ball off to the wall, height test with stadiometer in centimeter, ability test of shoot underbasket by shooting the ball to the basket ring. Product moment correlation and double correlation by perequisite test, normality test, and linerity test are used as data analysis technique. Based on the findings of this study, it can be concluded that there is a significant correlation between heel power toward shoot underbasket ability with coefission of correlation rx1y (0.496) in the significant level of 5%. There is a significant correlation between height and shoot underbasket ability with cefission of correlattion rx3y (0.498) in the significance level of 5%. There is a significant correlation between heel power, hands coordination, also height with shoot underbasket ability with the value ofÂ Â  Fhit (10.458)>Ftab (2.84) in the siginifincance level of 0.005.